Search Engines for Children Search User Interfaces and Information-Seeking Behaviour - Gossen, Tatiana (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2015)
The doctoral thesis of Tatiana Gossen formulates criteria and guidelines on how to design the user interfaces of search engines for children. In her work, the author identifies the conceptual challenges based on own and previous user studies and addresses the changing characteristics of the users by providing a means of adaptation. Additionally, a novel type of search result visualisation for children with cartoon style characters is developed taking children's preference for visual information into account. Contents  Information Retrieval for Young Users  Usability of Existing Search Engines for Young Users  Large-Scale Analysis of Children's Queries and Search Interactions  Differences in Usability and Perception of Targeted Web Search Engines between Children and Adults  Search User Interface Design for Children  Supporting Visual Searchers in Processing Search Results Target Groups< Target Groups  Lecturers and Students of Computer Science and Media Design, especially in the Field of Information Retrieval and Human-Computer Interaction  UI/UX Designer, Web Designer The Author Tatiana Gossen is a Postdoctoral Researcher at the Otto-von-Guericke University in Magdeburg.